2003
DOI: 10.1099/mic.0.26460-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of drug efflux genes by EvgAS, a two-component system in Escherichia coli

Abstract: A constitutively active mutant of histidine kinase sensor EvgS was found to confer multi-drug resistance (MDR) to an acrA-deficient Escherichia coli, indicating the relationship between the two-component system EvgAS and the expression of the MDR system. The observed MDR also depended on an outer-membrane channel, TolC. Microarray and S1 mapping assays indicated that, in the presence of this constitutive mutant EvgS, the level of transcription increased for some MDR genes, including the drug efflux genes emrKY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 34 publications
2
84
0
Order By: Relevance
“…1A) and third promoters; P 2 is 8 nucleotides downstream of P 1 , and P 4 is 12 nucleotides downstream of P 3 . The leader from P 1 is 111 nucleotides, and the leader of the second fusion (P 3 ) is 53 nucleotides in length (45,46). Similar to the acrA-lacZ fusion, the tolC-lacZ fusions starting either at the P 1 or P 3 start site were very active in the absence of arabinose on the MacConkey lactose agar plates (see Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…1A) and third promoters; P 2 is 8 nucleotides downstream of P 1 , and P 4 is 12 nucleotides downstream of P 3 . The leader from P 1 is 111 nucleotides, and the leader of the second fusion (P 3 ) is 53 nucleotides in length (45,46). Similar to the acrA-lacZ fusion, the tolC-lacZ fusions starting either at the P 1 or P 3 start site were very active in the absence of arabinose on the MacConkey lactose agar plates (see Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The number of copies per cell of AcrB is approximately 10-to 14-fold less than that of AcrA during the log phase of growth (4), further supporting the observation of significantly lower translation activity. In E. coli, tolC is reported to have four promoters (45,46). Translational fusions were designed to begin at the start sites for the first (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dosT frameshift mutation is not directly responsible for the constitutive DosR regulon overexpression phenotype. Since several previous studies have reported constitutively active mutations within sensor histidine kinases of bacterial 2CS systems (1,15,40,54), we decided to explore the possibility that the frameshift mutation in dosT results in constitutive activation of the DosR regulon for the group 2 to 5 W/Beijing strains. In order to test this, we overexpressed two distinct versions of dosT under the control of the hsp60 promoter within the H37Rv strain background.…”
Section: Vol 192 2010 M Tuberculosis Variation and Dost Sensor Kinmentioning
confidence: 99%
“…This system is associated with different pumps of RND family appearing in Gram-negative bacteria [8,25,60,81,86,94], among others AdeABC of Acinetobacter baumannii. Level of the expression of the pump, regulated by such a system, is dependent on the presence of the stimulus (substrate) in environment of the cell, which activating the pump for removing substrate outside the cell.…”
Section: Level Of Expressionmentioning
confidence: 99%